Teaching wrestling at school: proposal of a new pedagogical approach based on games for learning of technical moves - Hasan Melki; Mohamed S. Bouzid (IP Iermakov S.S., 2023)
Background and Study Aim. The purpose of this study was to find the effect of the game based on educational method and technical approach on the performance of legs attacks in free-style wrestling. Material and Methods. The type of research was semi-experimental. Participants included 20 boys' students who were divided into two groups based on the game-based approach (10) and technical training (10). The teaching unit was a format of 12 lessons over 4 weeks (2 days per week). Each lesson lasted 60 minutes. At the end of each training session, the participants played benchmark bouts, one on one, for 2 x 6 minutes. The data were analyzed using SPSS 16 software at a significance level of 0.05. Results. The results showed that both the game-based and technical approach groups had a significant improvement in successful leg attacks in free-style wrestling. With regard to the preparation of leg attacks, there was no improvement for the technical approach group.  However, the game-based group had a significant improvement in the total number of attacks compared to the technical group. Conclusions. The results suggest that the use of a game-based educational method can significantly increase the important factors of wrestling performance related to leg attacks in young wrestlers. Teachers can connect actions from other technical movements from the same family of leg attacks.